Edible Seaweeds: A Potential Novel Source of Bioactive Metabolites and Nutraceuticals With Human Health Benefits - Choudhary, Babita; Chauhan, O. P.; Mishra, Avinash (Frontiers in Marine Science, 2021)
There has been an increase in human health concerns, and seaweeds are considered as a potential functional food which can decrease the risk of many diseases, as they contain various bioactive compounds. Seaweeds are of nutritional interest and a rich source of natural bioactive compounds including antioxidants, flavonoids, phenolic compounds, and alkaloids that can be used as an alternative source of food material. Seaweeds contain a high amount of vitamins such as A, D, E, C, and B, and minerals including calcium, potassium, magnesium and iron. Seaweeds containing carrageenan, agar and other polysaccharides not only act as a source of fiber but also can act as prebiotics which may benefit the bacteria present in the large intestine. The lack of technologies to process seaweeds for human consumption at an industrial scale is a serious limitation on growth of the seaweed-based functional foods sector. Seaweeds are one of the most extensively used functional foods, with a long history in Asian countries. Now they are also being explored by many Western and European countries. Evidence from epidemiological research suggests that regular consumption of a marine algae-based diet may boost immunity against a number of diseases including COVID-19 novel virus by angiotensin-I-converting enzyme (ACE) inhibition.